Comparison of the effect of the Dietary Approaches to Stop Hypertension diet with usual dietary advice on expression of peroxisome proliferators-activated receptor gamma gene in women: A randomized controlled clinical trial - Mohammad Hasan Entezari; Rasol Salehi; Mohammad Kazemi; Mohsen Janghorbani; Marzieh Kafeshani (ARYA Atherosclerosis, 2018)
BACKGROUND: Peroxisome proliferator-activated receptor gamma (PPAR-γ) which controls body weight, glucose homeostasis, and adipocyte differentiation is a valuable candidate gene for insulin resistance (IR). The present study aimed to compare the effects of the Dietary Approaches to Stop Hypertension (DASH) diet and usual dietary advice (UDA) on PPAR-γ gene expression in women at risk for cardiovascular disease (CVD). METHODS: This randomized controlled trial was performed on 44 women aged 20-50 years at risk for CVD (BMI > 25 kg/m2 and low physical activity). Participants were randomly assigned to the UDA (n = 22) or DASH (n = 22) diets for 12 weeks. The DASH diet was rich in fruits, vegetables, whole grains and low-fat dairy products and low in saturated fat, total fat, cholesterol, refined grains and sweets, with a total of 2400 mg/day sodium. The UDA diet was a regular diet with healthy dietary advice. Anthropometric indices and PPAR-γ gene expression were measured and compared between the two groups at the end of the study. RESULTS: After the intervention, body mass index (BMI) and waist circumference (WC) significantly decreased in the DASH group (P < 0.050) but the results showed no significant differences between the two groups. At the end of the trial, PPAR-γ gene expression was significantly different between the UDA and the DASH diet groups (P = 0.040) and this difference remained significant after adjustment for BMI, and physical activity (P = 0.030). CONCLUSION: The result of the study showed that the DASH diet significantly decreased the expression of PPAR-γ. This finding was unexpected and future studies on the current topic are therefore recommended.